APLIKASI PETA KAWASAN RAWAN BENCANA (KRB) DALAM ANALISA SEBARAN KORBAN ERUPSI GA. MERAPI 2010 - Sari, Meassa Monikha (Program Studi Pendidikan Geografi STKIP PGRI Sumatera Barat, 2017)
The eruption of Merapi Volcano in 2010 was one of the biggest eruptions in the Merapi Volcano history. It caused several impacts such as building and environment damage, financial loss, and many casualties. The objective of this research is as a disaster mitigation by obtaining casualties distribution based on 2010 Disaster-prone Area map (Kawasan Rawan Bencana), knowing how the casualties distribution based on age and gender and getting the factors which caused many casualties. The research was done by quetionnaires, observation, field survey and interview with the casualties and stakeholders, then the data was analyzed using ArcMap software. The result of the research showed that distribution of the most casualties was in the around of Gendol River stream which was part of KRB III area about 260 persons. Meanwhile, 82 casualties were also spread in the KRB II area, 72 persons in the KRB I and non KRB area. The casualties in KRB III were caused by pyroclastic flow, and the others caused by tephra falls, accidents, disease, psychological condition and culture. Based on gender, men are many more than women and based on age, old men and women casualties are more than the younger casualties.